Iranian Education Modernization Strategy (Iran's Islamic Leader Renewal Movement in the Early 20th Century Study of Disclosure of Historical Facts through the Mass Media) - Faisal Musa; Muhammad Syukri; Datuk Imam Marzuki (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The modernization of Islamic education continues to be encouraged by structuring the Iranian education system based on the principles of Islamic teachings, without neglecting the modern education that has developed in the pre-revolutionary government, namely balancing religious education, science and technology. The process of modernization in Iran, especially those related to the modernization of Islamic education, educational renewal strategies, and aspects of being modernized are interesting to study. As an Islamic country that has successfully carried out a modernization revolution, it has made it equal to the western world. In this study, the authors tried to obtain material through information from the mass media, literature literature, namely collecting, reading and studying sources, obtaining material (library research) in the form of books. The method of discussion in this research is: Synthesis Analysis Method, namely by means of rational and abstract logical approaches to the objective of thinking inductively and deductively as well as scientific analysis.